Ozone initiated inactivation of Escherichia coli and Staphylococcus aureus in water: Influence of selected organic solvents prevalent in wastewaters. (September 2018) - Ofori, Isaac; Maddila, Suresh; Lin, Johnson; Jonnalagadda, Sreekantha B.
Abstract: Absorption, stability and reactivity of ozone in water are critical parameters to determine its efficiency in microbial inactivation. In this study, the influence of four water-soluble organic solvents commonly discharged from industrial lines into wastewater systems, namely; ethanol, methanol, ethyl acetate and dimethyl sulfoxide (DMSO) on the ozone-facilitated inactivation of Escherichia coli and Staphylococcus aureus in water was investigated. Ozone absorption (up to 12 min) as a function of ozone aeration time, and the decomposition rate were spectrophotometrically monitored in the presence of 2.5% and 5% concentrations of each organic solvent. Their consequent effect on bacterial inactivation was determined. The inactivation kinetics were described using the efficiency factor Hom model. Residual concentrations of absorbed ozone in solutions with ethyl acetate or DMSO were relatively higher than those in methanol or ethanol-containing solutions. DMSO and ethyl acetate enhanced the stability of ozone in water, characterised by a lower decomposition rate constant in DMSO ( k d  = 3.81 × 10 −2  M −1  s −1 ) and ethyl acetate ( k d  = 4.45 × 10 −2  M −1  s −1 ) solutions, in contrast with that in methanol ( k d  = 1.13 × 10 −1  M −1  s −1 ), where the decomposition rate was higher. The faster absorption and stability of ozone in ethyl acetate and DMSO corresponded with an observed increase in the log inactivation of E. coli and S. aureus by approximately 2-fold relative to that in methanol. Highlights: Methanol accelerates ozone decomposition rate in water. 5% (v/v) ethanol, methanol, ethyl acetate and DMSO marginally impact on bacterial disinfection. Increased absorption and stability of ozone enhances its bacterial inactivation efficiency. Ethyl acetate and DMSO enhance absorption and stability of ozone in water.